Metode Pendidikan Islam Dalam Perspektif Filsafat Pendidikan Islam - Ahmad Sukri Harahap (Sekolah Tinggi Agama Islam Sumatera Medan, 2018)
In the western perspective there are so many election methods offered by educational figures. But it is necessary to note that sometimes the method does not match the characteristics of human nature. Specifically, the Islamic educational method must be relevant to the human nature as a dual dimensional being, consisting of jism and spirit and the Islamic conception of the way of the coming of knowledge into man through hearing (sam'a), sight (bashar) and heart (qalb ). If this is not considered, then no matter how well the method is chosen, it may not be able to solve the problem.